How to eliminate pathogen without killing oneself? Immunometabolism of encapsulation and melanization in Drosophila - Dolezal, Tomas (Frontiers in Immunology, 2023)
Cellular encapsulation associated with melanization is a crucial component of the immune response in insects, particularly against larger pathogens. The infection of a Drosophila larva by parasitoid wasps, like Leptopilina boulardi, is the most extensively studied example. In this case, the encapsulation and melanization of the parasitoid embryo is linked to the activation of plasmatocytes that attach to the surface of the parasitoid. Additionally, the differentiation of lamellocytes that encapsulate the parasitoid, along with crystal cells, is accountable for the melanization process. Encapsulation and melanization lead to the production of toxic molecules that are concentrated in the capsule around the parasitoid and, at the same time, protect the host from this toxic immune response. Thus, cellular encapsulation and melanization represent primarily a metabolic process involving the metabolism of immune cell activation and differentiation, the production of toxic radicals, but also the production of melanin and antioxidants. As such, it has significant implications for host physiology and systemic metabolism. Proper regulation of metabolism within immune cells, as well as at the level of the entire organism, is therefore essential for an efficient immune response and also impacts the health and overall fitness of the organism that survives. The purpose of this "perspective" article is to map what we know about the metabolism of this type of immune response, place it in the context of possible implications for host physiology, and highlight open questions related to the metabolism of this important insect immune response.